Funkcional'naja podgotovlennost' sportsmenov akademiceskoj grebli v processe podgotovki i otbora k otvetstvennym sorevnovanija - Iordanskaja, F. A.; Abramova, T. F.; Bucina, E. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
On group of 99 elite rowers of different sex and age (65 men, 34 women) conducted research on the development and implementation of a diagnostic program for functional preparedness and the development of criteria for assessing the prognosis and selection for major competitions. For the first time, the role of vegetative orthostatic stability of oarsmen in the formation of training, concentration of attention and synchronization of crew work is shown. The criteria for evaluationof cardiovascular and vegetative nervous system parameters and their adaptation to test loads are determined, characterizing the development of fitness and increasing adaptation to loads. Weak links of adaptation and indicators that limit the performance of athletes rowing are identified.